If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11(2x + -5) = 0 Reorder the terms: -11(-5 + 2x) = 0 (-5 * -11 + 2x * -11) = 0 (55 + -22x) = 0 Solving 55 + -22x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-55' to each side of the equation. 55 + -55 + -22x = 0 + -55 Combine like terms: 55 + -55 = 0 0 + -22x = 0 + -55 -22x = 0 + -55 Combine like terms: 0 + -55 = -55 -22x = -55 Divide each side by '-22'. x = 2.5 Simplifying x = 2.5
| 2x-62=106 | | x=7x-154+33+(11*11) | | 0=(4y-y^2)/(y^2-4) | | 4x+36=12x/60 | | 2x-22=114 | | 4(6-w)=3(2w+2) | | 5+3m=5m-19 | | 231-4x=41x+21 | | 6(2x-4)-3x=15 | | y=3x^2+42x-56 | | 4y+7=-22+y | | p^2-5p-17=7 | | 2-3y=9-8y | | 2n+-1=3(n-m) | | 5/4x-18 | | 51-6x=3x+23 | | 18x+5/4 | | 1x+10=28+x | | 6+2x=1-3x | | 5/4x+18x | | 5/4x+18 | | -13-8x=7x+13 | | x/2+3=2x | | 1=(3/(y+2))+(1/(y-2)) | | 2x+45=95 | | x^2(2x+5)+17(2x+5)= | | 3/5x+12=6 | | x/4-5=10 | | 25p-40=160 | | 25p+40=160 | | x^2(x-3)+12(x-3)= | | 40p-25=160 |